Effects of Different Strategies for Delivering Supplemental Zinc on Selected Fecal Markers of Environmental Enteric Dysfunction Among Young Laotian Children (P04-012-19). (13th June 2019) - Hinnouho, Guy-Marino; Wessells, K Ryan; Barffour, Maxwell; Sayasone, Somphou; Arnold, Charles; Kounnavong, Sengchanh; Brown, Kenneth; Hess, Sonja
Abstract: Objectives: To assess the impact of different strategies for delivering supplemental zinc on fecal myeloperoxidase (MPO), neopterin (NEO) and calprotectin (CAL) among young Laotian children and explore modifying effects of MPO, CAL and NEO on growth Methods: In a double-blind controlled trial, children 6–23 mo of age were randomized to receive either daily preventive zinc tablets (PZ; 7 mg/d), daily micronutrient powder sachets (MNP; containing 10 mg zinc and 14 other micronutrients), therapeutic zinc supplements for diarrhea treatment (TZ; 20 mg/d for 10 days) or daily placebo powder and followed for ∼36 weeks. Stool samples were collected at baseline and endline. Fecal MPO, NEO and CAL were determined in a randomly selected sub-sample of 720 children using commercially available ELISA kits. Linear regression models were used to assess main and modifying effects while controlling for baseline value, age and district Results: The baseline prevalence of stunting was 39.3%, and there was no overall treatment effect on physical growth in the parent trial. At endline, geometric mean fecal MPO, NEO and CAL concentrations did not differ among the 4 groups (all P  > 0.23). There was an effect modification by baseline concentrations of NEO and CAL on endline stunting (p for interaction = 0.01 and 0.02, respectively). Among children in the lowest quintile of NEO concentrations, there was a trend towards a higher stunting prevalence at endline in the TZ [47.1% (35.6, 58.7)] and the MNP [45.3% (32.7, 57.9)] groups compared to the PZ [33.6% (21.0, 46.3)] and the control [33.9% (22.8, 44.9)] groups. Similar results were found among children in the lowest quintile of CAL concentrations. Moreover, baseline concentration of CAL, modified the impact of the interventions on weight-for-height z-scores (WHZ) (p for interaction = 0.074). Among children in the lowest quintile of CAL concentrations, there was a trend towards a higher WHZ at endline in the MNP [−0.57 (−0.73, −0.42)] and TZ [−0.68 (−0.86, −0.51)] groups compared to the control [−0.79 (−0.97, −0.61)] and the PZ [−0.88 (−1.05, −0.72)] groups. Conclusions: In this population of young Laotian children PZ, MNP and TZ had no overall impact on EED or growth, but intestinal function modified the growth response to supplementation suggesting its potential role in the pathways of growth impairment. Funding Sources: Funded by the Bill & Melinda Gates Foundation, Nutrition International and the Mathile Institute for the Advancement of Human Nutrition.